San Salvatore di Pavia and Santa Maria di Pomposa: Patrimonial, Political and Documentary Logics of a Conflictual Relationship (Late 10th - Early 12th Cent.) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2024)
A broad and varied documentary tradition allows for the compilation of a dossier of public documents concerning the relationship, as close as it was conflictual, that linked Pomposa to the royal monastery of S. Salvatore in Pavia. The dossier of originals and copies, not devoid of falsifications and manipulations, at first glance seems to present a contradictory picture and a somewhat irrational narrative, in which various kings, emperors, and empresses would have alternately assigned the possession of Pomposa now to the monastery of Pavia, now to the Archbishop of Ravenna, now to both simultaneously, and at times brought it back under direct imperial control. The move beyond a strictly legal-historical approach to the history of public institutions, their patrimonies, and their documentation, along with the integration of diverse perspectives from more recent historiographical and diplomatic research, allows the issue to be approached in a renewed manner. The dossier offers a highly interesting case for the study of royal policies in the management of fiscal patrimony, for understanding the political and structural investment of the Ottonians in the Exarchate, and for the political history of the kingdom of Italy around the year 1000—while also shedding light on the strategies for defending public-origin patrimonies that were implemented in the 12th century, when the kingdom as a system had already declined.
Keywords: S. Salvatore di Pavia; Pomposa; Otto III; empress Adelaide; fiscal estates